Causal Relationship Between Sleep Traits and Hypothalamic-Pituitary-Target Gland Axis Function: A Mendelian Randomization Study - Ren Z; Long J; Deng W; Jing Y; Qiu J; Ren W; Liu D (Nature and Science of Sleep, 2024)
Ziyu Ren,1 Jiangchuan Long,1 Wenzhen Deng,1 Yuanyuan Jing,1 Jingwen Qiu,1 Wei Ren,2 Dongfang Liu1 1Department of Endocrinology and Metabolism, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Endocrinology and Metabolism, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Wei Ren, Department of Endocrinology, The First Affiliated Hospital of Chongqing Medical University, No. 1. You-Yi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +86-23-89012755, Email renwei67@sina.com Dongfang Liu, Department of Endocrinology, The Second Affiliated Hospital of Chongqing Medical University, No. 74, Linjiang Road, Yuzhong District, Chongqing, 400010, People’s Republic of China, Tel +86-23-63832133, Email 300306@hospital.cqmu.edu.cn; ldf023023@qq.comBackground: In recent years, multiple observational studies have confirmed the association between sleep traits and various human physiopathological states. However, the causal relationship between sleep traits and hypothalamic-pituitary-target gland axis (HPTGA) function remains unknown.Methods: We obtained summary statistics on sleep traits (insomnia, chronotype, and sleep duration (long and short)) from the UK Biobank database. Data related to the HPTGA functions were obtained from the publicly available database. Subsequently, a two-sample Mendelian randomization (MR) analysis was performed to investigate the causal relationship between different sleep traits and the HPTGA function. Reverse MR analysis was conducted to examine the direction of causality.Results: The MR analysis results suggested that chronotype is associated with decreased levels of six hormones in HPTGA. Sleep duration was causally associated with decreased levels of free thyroxine and progesterone. Both long and short sleep durations are detrimental to the secretion of prolactin-releasing peptide, somatostatin, and plasma cortisol, while short sleep duration can promote progesterone secretion. After gender stratification, we found that female reproductive function is more susceptible to the influence of unfavorable sleep traits.Conclusion: Our MR analysis indicated a significant causal association between chronotype and suppressed gonadal function in healthy adult humans, with no apparent gender-specific effect. Extreme sleep durations were also found to be detrimental to the maintenance of normal HPTGA secretion function. Compared to males, gonadal function in the female cohort is more susceptible to extreme sleep habits. Subsequent observational studies are urgently needed to confirm the underlying mechanisms.Keywords: hypothalamo-hypophyseal-target gland axis, sleep traits, causal inference, Mendelian randomization